KALEIDOSCOPE OF THE DUALISM OF LIGHT AS A FORM OF SELF-RESPECT WITH THE UNIVERSE VERSES - Nugraha, Dwi Apriyadi (EduFisika: Jurnal Pendidikan Fisika, 2022)
The author made this research with the intention of reviewing the literature regarding the dualism of light as a form of appreciation for the verses of the universe. The research method uses a literature review. The collection of information sources is done by collecting books, articles, journals that are relevant, then it is examined for suitability with the title. The results of this research show that the dualism of light can be a springboard to better appreciate the verses of the universe. This can be seen from the many similar conclusions expressed by previous researchers, and the sources of information that support it.